How do Gestures Actualize Young Learners’ Affection: Sympathizing George’s Gestures as Depicted in The Slithery Day - Sumekto, Didik Rinan (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research targets articulating George’s gestural expressions that contribute to young learners’ affection. Teaching values become the turning point in children’s behavioral learning processes where they can comprehend the values as adaptable as possible towards supportive environments. Data collection was primarily undertaken from George’s The Slithery Day episode linked to the YouTube web. Data analysis was adjustably analyzed through George’s visually gestural expressions that initiated its positive and constructive speech acts accordingly. However, Oliveira’s (2009) directives options use of imperatives, declarative, and interrogatives were attributed to accomplishing the content analysis. The results record that George’s gestural expressions might teach young learners about showing hospitality and helping to each other, setting off innovativeness with the variously tiring endeavors, eagerly willing to know something new as addressing life skills, and respecting someone else creations, as well as performing the capability of conveying, promising, asking, demanding, commanding, requesting, complaining, and announcing that supported the empirical speech acts. These gestural expressions afford the functional, observable, workable, concrete, and empirical positions as if showing the recognizable relationships and the goodness in George’s interactions with others. However, George’s experientially gestural expressions symbolized non-verbal communication agreements to the significance of young learners’ sensitive adaptability in their daily learning and interaction processes.